Pengaruh Pengetahuan Akuntansi, Kepribadian Kewirausahaan, dan Latar Belakang Pendidikan Terhadap Laporan Keuangan UMKM Potorono Edupark - Maulida Putri Ayuningtyas; Budiantara, Martinus (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to find and analyze how accounting is used in MSMEs and the issues or problems they face. This research uses quantitative methods with a descriptive approach, the population is MSMEs located around Potorono Edupark as the research location with 30 samples of MSME actors. The method used is multiple linear regression analysis. Based on the T Test, the research results show that accounting knowledge does not have a significant influence, entrepreneurial personality has a significant influence and educational background also has a significant influence on the development of MSMEs. So it can be concluded that MSME business owners should keep records to support their business because apart from being important for business, the application of accounting can also be used by MSME owners in making decisions.